2004
DOI: 10.1128/jvi.78.15.8404-8410.2004
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Latent Membrane Protein 1 (LMP-1) Half-Life in Epithelial Cells Is Down-Regulated by Lytic LMP-1

Abstract: This study examined the effect of naturally occurring Epstein-Barr virus (EBV) latent membrane protein 1 (LMP-1) gene sequence variation on the LMP-1 half-life in epithelial cells. The LMP-1 half-life was not influenced by sequence variation in amino acids 250 to 307 or amino acids 343 to 352. The LMP-1 half-life was short when the amino acid encoded at position 129 was methionine, the initiation codon product of lytic LMP-1 (lyLMP-1). The mutation of amino acid 129 to isoleucine greatly increased the LMP-1 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The results of this study also lend strong support to the hypothesis that lyLMP-1 exerts its down-regulatory effect on LMP-1 by promoting LMP-1 degradation and thereby reducing the quantity of LMP-1 available to generate oncogenic signals. In this study, we demonstrated a dose-dependent reduction in LMP-1 oncogenic activity by lyLMP-1 that mirrors the previously demonstrated dose-dependent reduction in LMP-1 half-life by lyLMP-1 (24). More importantly, we demonstrated a reduction in expressed LMP-1 quantity by lyLMP-1.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The results of this study also lend strong support to the hypothesis that lyLMP-1 exerts its down-regulatory effect on LMP-1 by promoting LMP-1 degradation and thereby reducing the quantity of LMP-1 available to generate oncogenic signals. In this study, we demonstrated a dose-dependent reduction in LMP-1 oncogenic activity by lyLMP-1 that mirrors the previously demonstrated dose-dependent reduction in LMP-1 half-life by lyLMP-1 (24). More importantly, we demonstrated a reduction in expressed LMP-1 quantity by lyLMP-1.…”
Section: Discussionsupporting
confidence: 71%
“…Taken together, these results indicate that clone K confers a greater growth and survival advantage to epithelial cells than does clone B958WT at all three serum concentrations and that lyLMP-1 completely reverses the growth and survival advantage of clone K. tein quantities are determined not only by the quantity of each plasmid transfected and its relative transfection efficiency but also by the relative rates of synthesis and degradation for each protein. It is especially difficult to determine the stoichiometry of a protein-protein interaction when one of the coexpressed proteins acts to promote the degradation of the other, as lyLMP-1 does to LMP-1 (24) and as LMP-1 may do to lyLMP-1 (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigenic analysis indicated that this variant sequence (YFLEILWRL) was not only poorly recognized by epitope-specific CTL but also showed significant loss in HLA A2 binding compared to the B95-8 sequence [25]. Pandya and Walling [48] showed that the amino acid change at codon 129 (Met to Ile) increased the LMP1 half-life in epithelial cells. It is likely that the variant sequence at codon 125-133 (YFLEILWRL) may be selected in nasal NK/T-cell lymphoma as well as NPC and may play important roles in reduced recognition of CTL and/or in lymphomagenesis.…”
Section: Discussionmentioning
confidence: 97%
“…[28]). Wild-type LMP1 constitutively signals when assembled at cellular membranes and has a half-life of 4–8 h [29]. Using our inducible model of mCD40–LMP1-induced signaling, we show LMP1-mediated expression of both isoforms of Pim1 after 2 h, well within the surface membrane half-life of wild-type LMP1, and with similar kinetics to CD40 induction of Pim1 expression (2 h) [30].…”
Section: Discussionmentioning
confidence: 98%